Employee Information System (SIP): The role of work motivation, communication and coordination in improving employee performance - Silitonga, Witler Slamat Halomoan; Madiistriyatno, Harries (International Journal of Artificial Intelligence Research, 2023)
Employee Information System (SIP) is a system designed to manage information related to employees in an organisation or company. The main purpose of the Employee Information System is to assist in managing employee data efficiently and effectively. The aim of the study was to determine the effect of work motivation, communication and coordination partially on performance and to determine the effect of work motivation, communication and coordination simultaneously on the performance of employees of the Bekasi City Sharia Cooperative. The method used is data collection methods and data analysis methods using statistical calculations. The regression coefficient value of Work Motivation b1 = 0.137, has a tcount value of 1.237 and probability Sig = 0.223 Ëƒ 0.05, then the value of the regression coefficient of work motivation is said to be insignificant and can be interpreted that if work motivation increases by one unit, employee performance increases by 0.137 units assuming constant communication and coordination. Communication regression coefficient b2 = 0.314, has a t-count value of 2.362 and probability Sig = 0.023Ëƒ0.05, then the value of the communication regression coefficient is said to be insignificant and can be interpreted that if communication increases by one unit, employee performance increases by 0.314 units with assumption of constant work motivation and communication. The value of the coordination regression coefficient b3 = 0.387, has a t-count value of 3.147 and the probability Sig = 0.003 Ëƒ 0.05, then the value of the coordination regression coefficient is said to be significant and can be interpretednamely if coordination increases by one unit, employee performance increases by 0.387 units with the assumption constant work motivation and communication. This study contributes to work motivation, communication and coordination simultaneously on employee performance. The effect of work motivation, communication and coordination on performance simultaneously is shown by the results of the analysis, that the effect of work motivation, communication and coordination is shown by the value of the regression coefficient b1 = 0.137; b2 = 0.314; and b3 = 0.387. Significant value at the 5% test level because it has F count Ëƒ F table (16.184Ëƒ2.833) and sig É‘ (0.000Ë‚0.05). The consequences of this study are limited to the research variables of work motivation, communication, coordination, and employee performance. In addition, the object of research is only within the scope of the Bekasi City Sharia Cooperative.Â